An Analysis of Students’ Problems in Reading Comprehension at SMK Negeri 1 Gorontalo - Ariani Prihatmini Pakaya; Rasuna Rasid Talib; Sri Rumiyatiningsih Luwiti; Sartin T. Miolo; Rahmawaty Mamu (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to identify and thoroughly analyze the specific reading comprehension problems faced by tenth-grade vocational students at SMK Negeri 1 Gorontalo within the implementation of Kurikulum Merdeka. The research employed a descriptive qualitative methodology utilizing the interactive data analysis model framework. The participants consisted of 21 tenth-grade vocational students (Batch 2023). Data were collected using a 42-item Likert-scale diagnostic questionnaire administered via Google Forms, complemented by semi-structured interviews with 10 selected key respondents. The theoretical foundation was grounded in Duke and Cartwright's Active View of Reading model. The findings revealed a severe "linguistic bottleneck" where 85.7% of students struggled significantly with unfamiliar vocabulary, forcing 90.4% to rely heavily on mechanical word-for-word translation. Furthermore, 71.4% experienced cognitive overload when encountering complex sentence structures and multi-clause syntactic patterns. Externally, an instructional gap was prominent, with 76.1% of students highlighting a critical deficiency in visual or multimodal learning media in the classroom. Conversely, cultural schema activation acted as a major catalyst; 80.9% exhibited high motivation when reading local folklore. The study concludes that vocational reading failure is primarily driven by linguistic barriers and instructional limitations rather than motivational apathy, emphasizing an urgent need for multimodal scaffolding in vocational EFL contexts.